Cara Pembuatan Komposter Rumahan Sederhana - Rida Respati; Hendra Cahyadi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2018)
The increase in population in Palangka Raya each year results in an increase in the waste produced. The increase in the amount of garbage was apparently not followed by an increase in temporary waste disposal facilities (TPS). Based on the results of previous research it was found that for the Pahandut Subdistrict of Palangka Raya City the waste generation produced was not comparable to the capacity of the TPS capacity. It was stated that the capacity of the TPS was only 45% of the waste generation that occurred per day. As a result, a lot of garbage is scattered outside the TPS and some are dumped into rivers and drainage channels. Based on the foregoing, a proposal arises to reduce the problem of waste generation. One such proposal is to reduce the initial source of waste from individual households. However, to reduce household waste, of course, it needs an effort to provide knowledge to the public about the waste sorting efforts that occur. Community participation in addressing the problem of municipal waste is very dominant, and this level of participation should be the main barometer in future waste management. To increase the role of the community in dealing with waste issues we propose an idea as a solution. The idea is to utilize household waste into compost. For this reason, it is necessary to provide a socialization on how to make compost from household waste. Therefore we made socialization with the topic of How to Make Simple Home Composter.